Functionalized Fluoropolymer Membrane for Fuel Cell Applications - Prakash O.; Pandey A.K.; Maiti P. (My University, 2025)
Polymeric membrane has been the key component of research in view of the fact that previous few decades had newest enhancement in both production and design aspect. Porous and nanochannel developed polymeric membranes have put on much interest in this viewpoint for their consumption in a various sectors such as adhesive, sensor, biotechnology, waste water treatment including separation techniques, and ion exchange membranes (IEMs) for polymer electrolytes membrane fuel cell (PEMFCs), because of their good thermal and outstanding mechanical properties along with electrical properties when properly functionalized with some functional group. This chapter mainly focuses on the research work being conducted on fabricating porous polymeric membranes followed by the functionalization and subsequently their applications in the field of fuel cell technology as electrolyte membranes. In this context, swift heavy ions (SHI) bombardment on the polymeric membrane, design the porous membranes having controlled channel dimension using ions of different size, nanoparticle and fluence variation. The effect of SHI on the polymeric membrane creates reactive sites (free radicals) which are utilized to functionalize the application of fuel cell membrane. However, the aim of this book chapter is to discuss the fabrication of porosity in polymer membrane and subsequent functionalization for energy applications especially in fuel cell technology. © The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2022.